LEGAL FRAMEWORK OF EMERGENCY SITUATIONS IN THE AUTONOMOUS PROVINCE OF VOJVODINА - Ivetić, Zorana; Tošić, Jovanka (Poslovna ekonomija, 2025)
Emergency situations are an element of every state and society, including the Republic of Serbia and its Autonomous Province of Vojvodina. Whether triggered by natural disasters or human actions, such crises result in significant loss of life, severe environmental damage, and substantial material losses. Defining an adequate legal framework for emergency situations is a key element of managing emergency situations and protecting the population from various threats, including natural disasters, technological breakdowns, epidemics and various social conflicts. The subject of research in this paper is emergency situations, more precisely, the analysis of legal regulations related to emergency situations in the territory of the Autonomous Province of Vojvodina, with an emphasis on the Law on Disaster Risk Reduction and Emergency Management. The positive legal method and the logical methods of induction and deduction were used in the analysis.